Long-Term Temporal and Spatial Distribution of Coliform Bacteria in Jiaozhou Bay Associated With Human Activities and Environmental Governance - Kaixuan Cui; Yi Dong; Xiaoxia Sun; Li Zhao; Haijian Du; Jia Liu; Chaofeng Wang; Chen Liang; Yicong Zhao; Si Chen; Jun Xuan; Suheng Li; et al. (Frontiers in Marine Science, 2021)
Coliform bacteria (CB) can be used as an indicator of seawater quality. Long-term monitoring of seawater quality based on CB abundance is lacking in Jiaozhou Bay. In this study, CB abundance in surface seawater of 12 different stations in Jiaozhou Bay was investigated by culturing method. The results showed that: (1) the abundance of CB showed a decreasing tendency during the investigation. During 2004–2007, 2008–2013, and 2014–2017, the average CB abundance decreased significantly, forming a “three stages phenomenon”; (2) the average CB abundance in the first half of the year was lower than that in the second half; (3) the CB abundance in Jiaozhou Bay was spatially heterogeneous. The maximum average CB abundance was observed in the estuary area, and followed by the bay mouth area, the outer bay area, and the inner bay area. The highest abundance may be associated with sewage discharge related to human activities; (4) the abundance of CB was most positively correlated with the concentration of ammonium salt and nitrate, while most negatively correlated with salinity; (5) the years 2007 (2008) and 2013 (2014) were time points of the “three stages phenomenon.” These time points coincide with environmental governance actions, indicating that the actions have played a prominent role in improving seawater quality. Long-term survey of CB can not only serve as an indicator of seawater quality, but also provide a basis for the development of environmental governance strategies and pollution control.